2015
DOI: 10.3390/ijerph13010004
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Participatory Research Integrates Behavioral and Biological Research to Achieve Health Equity for Native Hawaiians

Abstract: Native Hawaiians bear a disproportionate burden of type-2 diabetes and related complications compared to all other groups in Hawai‘i (e.g., Whites, Japanese, Korean). Distrust in these communities is a significant barrier to participation in epigenetic research studies seeking to better understand disease processes. The purpose of this paper is to describe the community-based participatory research (CBPR) approach and research process we employed to integrate behavior and biological sciences with community hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…One pilot study with a wait-list control group in Native Hawaiians showed that culturally adapted diabetes self-management education building on culturally relevant knowledge and activities (i.e. groupbased educational format to facilitate social support, convenient community location, delivered by local community members in the local language, incorporation of local images/food/common physical activities/local people to increase relevance) for 3 months improved A1C, diabetes understanding and diabetes selfmanagement (97,98). In a qualitative study in rural Australia, participants reported both negative influences (i.e.…”
Section: Managementmentioning
confidence: 99%
“…One pilot study with a wait-list control group in Native Hawaiians showed that culturally adapted diabetes self-management education building on culturally relevant knowledge and activities (i.e. groupbased educational format to facilitate social support, convenient community location, delivered by local community members in the local language, incorporation of local images/food/common physical activities/local people to increase relevance) for 3 months improved A1C, diabetes understanding and diabetes selfmanagement (97,98). In a qualitative study in rural Australia, participants reported both negative influences (i.e.…”
Section: Managementmentioning
confidence: 99%
“…Community-based organizations.-The involvement of community leaders through community-based organizations was discussed in 80% of the articles. [62][63][64][65][66][67]69,70,[98][99][100][101][102][103][104][105][106][107][108][109][110][111][112]116,117,[120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136] The involvement of community-based organizations was cited as a way to leverage, build, and sustain leadership within the Pacific Islander community. 81 Community-based organizations (e.g., federally qualified community health centers and grassroots non-profit community-based organizations) were described as playing a direct role in the research design, study conduct, and dissemination of the results back to the community.…”
Section: Engaging Community Leadersmentioning
confidence: 99%
“…Community advisory board.-More than half (54%) of the reviewed articles mentioned partnering with a community advisory board. 62,[64][65][66][67]69,70,[72][73][74][75][76][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112]116,117,[120][121][122][123]…”
Section: Engaging Community Leadersmentioning
confidence: 99%
See 1 more Smart Citation
“…They recommended that academic institutions must reach out to local community groups and together address local health issues that affect the community. Townsend and collaborators [9] conducted a CBPR to better understand and address the disproportionate burden of type-2 diabetes and related complications among Native Hawaiians compared to all other groups in Hawaii (e.g., Whites, Japanese, Korean). Their study findings stressed the importance of securing the thrust of communities for research participation, and engagement in health assessments and disease control and prevention.…”
mentioning
confidence: 99%